Pengaruh Komunitas Virtual Terhadap Perubahan Perilaku Remaja - Yuliani Yuliani (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
In today's digital era, there is less and less direct interaction and more and more people join virtual communities. So that virtual communities can form a change in behavior in adolescents with several factors including: personality factors, emotional factors, peer factors, environmental factors. This research uses a literature study by comparing and adding references from literature sources. The purpose of this study was conducted to determine changes in adolescent behavior in virtual communities and what the factors are. The results of this study indicate that behavior change is a change that a person experiences in an environment, due to a response or stimulus from a person in a community so that in here it can be seen in the virtual community of adolescents through the IT world can form a change based on four factors including personality, emotions, peers and the environment.